The Capability Paradox: When Competence Becomes a Risk in Public Leadership: Paradoks Kapabilitas: Ketika Kompetensi Menjadi Risiko dalam Kepemimpinan Publik - Ismail, Ismail (Edumaspul: Jurnal Pendidikan, 2026)
This conceptual paper examines the Capability Paradox, a condition in which competence, experience, and institutional expertise in public leadership may serve as sources of public value while simultaneously creating risks of authority abuse. Public sector competence has commonly been viewed as a prerequisite for bureaucratic effectiveness, public sector innovation, and accountable service delivery. However, in complex public organizations, competence does not automatically lead to good governance when it is not guided by integrity, accountability, and effective oversight. This study employs a conceptual method with a theory-building approach to develop a theoretical framework explaining the relationship between competence, administrative capability, integrity, accountability, and corruption risk. Drawing on literature in public administration, fraud theory, public integrity, accountability, and digital governance, this article proposes the Capability–Integrity Equilibrium Theory (CIET). CIET argues that administrative capability is ambivalent: it can generate public value when directed by a strong ethical governance filter, but it can also turn into corruption capability when embedded in weak ethical environments. The main contribution of this study lies in extending the concept of capability from an individual attribute in the Fraud Diamond into an institutional capacity shaped by positional experience, structural authority, access to information, actor networks, and mastery of organizational procedures. The article argues that public sector reform should not focus solely on improving bureaucratic competence, but must also establish equilibrium among capability, integrity, accountability, and oversight to ensure that competence remains aligned with the public interest.